2019
DOI: 10.4103/jfmpc.jfmpc_452_19
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of aromatherapy on mental, physical symptoms, and social functions of females with premenstrual syndrome: A randomized clinical trial

Abstract: Objective:This study was designed to compare the effect of aromatherapy with Rosa Damascena and Citrus Aurantium blossom on psychological and physical symptoms and social functions of females with premenstrual syndrome.Materials and Methods:This double-blind clinical trial was conducted on 95 students. They were randomly divided into three aromatherapy groups (aromatherapy with 4% concentration of Rosa Damascena and 0.5% concentration of Citrus Aurantium blossom essential oil) and aromatherapy with sweet almon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…Also, the improvement of sleep quality was more notable in the damask rose group compared to the placebo group. These findings substantiate the available data regarding the effect of damask rose aromatherapy on improving patients' sleep quality [28][29][30]35 . However, previous studies found no significant effect for inhalation aromatherapy with damask rose on the sleep quality of healthy individuals 47,48 , which is inconsistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Also, the improvement of sleep quality was more notable in the damask rose group compared to the placebo group. These findings substantiate the available data regarding the effect of damask rose aromatherapy on improving patients' sleep quality [28][29][30]35 . However, previous studies found no significant effect for inhalation aromatherapy with damask rose on the sleep quality of healthy individuals 47,48 , which is inconsistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…Limited studies have been performed to concurrently evaluate the impact of damask rose aromatherapy on both sleep quality and anxiety 29,35 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, four studies measured state anxiety by the visual analog scale for anxiety (VASA, score: 0-10) (Amini & Alizadeh, 2018;Davaneghi et al, 2017;Kheirkhah et al, 2014;Seyyed-Rasooli et al, 2014). The remaining seven studies used different measures of state anxiety (Bikmoradi et al, 2021;Daneshpajooh et al, 2019;Dehkordi et al, 2017;Heydari et al, 2019;Jamilian et al, 2013;Noorian et al, 2020;Premkumar et al, 2019). The data of two publications, which used SAI and VASA among the same participants, were pooled in the overall analysis to count individual participants in the meta-analysis only once (Kheirkhah et al, 2014;Setayeshvali Pour et al, 2012).…”
Section: Anxietymentioning
confidence: 99%
“…In candidates of hemodialysis (HD), stress and anxiety levels were significantly lower after inhalation of RDM, but depressive symptoms reduced non-significantly . On the contrary, depression levels of college students with premenstrual syndrome (PMS) reduced significantly following the inhalation of RDM, but the intervention had no significant effect on their anxiety levels (Heydari et al, 2019). Furthermore, oral administration of Jollab (an extract of RDM) significantly reduced depression amongst patients suffering from functional dyspepsia (Pasalar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, for the management of PMS, various medical and non-medical interventions are recommended (Appleton, 2018;Bahrami et al, 2018;Heydari et al, 2019;Maleki-Saghooni et al, 2018;Tully et al, 2020;Yilmaz-Akyuz & Aydin-Kartal, 2019).…”
mentioning
confidence: 99%